Opening a niche for therapy: local lymphodepletion helps the immune system to fight melanoma - Mahnke, Karsten; Skorokhod, Alexander; Grabbe, Stefan; Enk, Alexander (The journal of investigative dermatology, 2014)
In this issue, Fujiwara et al. report that local ablation of CD4+ T cells in a murine B16 melanoma model, together with concomitant activation of the immune system by OX40L, leads to complete rejection of the melanomas. Rejection was driven mainly by CD8+ T cells, which infiltrated the melanomas and secreted sizeable amounts of IFN-γ. However, CD8+ T-cell infiltration also caused the recruitment of immunosuppressive myeloid-derived suppressor cells (MDSCs). Although these cells did not prevent the rejection of the melanomas, in clinical settings the long-term repopulation of tumors by MDSCs may counteract successful treatment. Thus, local ablation of CD4+ leukocytes may improve anti-melanoma therapies in humans, but at the same time MDSC levels in the tumor cells have to be kept in check to ensure treatment success.
Available online 8 December 2015
Gesehen am 22.07.2020